Sejarah Lokal Riau untuk Pengembangan Materi Ajar Sejarah Indonesia Kelas XI SMA - Asyrul Fikri (Universitas Negeri Padang, 2019)
Results of the study aims to integrate local history that is in the Riau into festive the history of Indonesia material of class XI. The method used is the analysis of documents, namely documents the history of Indonesia syllabus of class XI. Historical events that happened in Riau are integrated and analyzed to each basic competence in accordance with the learning material. Results of the study are, among others, the local people's struggle history of Riau do resistance to colonization a foreign nation such as the people's resistance war Guntung, war Reteh, war Mondang Kumango, resistance Tuanku Tambusai, resistance Datuk Tabano, Resistance Raja Haji, Sultan Zainal Abidin, War and resistance Manggris and Pirates in waters of Riau can be integrated into the basic competence to analyze the process of entry and the development of European colonization (Portugal, Spain, Netherlands, United Kingdom) to Indonesia with the material of Learning Strategies of resistance against Indonesia nation of European colonialism until the beginning of the 20th century. Integration of the study of local history in the process of learning history in class is expected to improve the understanding and awareness of the students against the local local history and its relationship with national history.